cGMP induces phase shifts of a mammalian circadian pacemaker at night, in antiphase to cAMP effects. - Prosser, R A (1989)
The suprachiasmatic nuclei (SCN) of mammals contain a circadian clock that synchronizes behavioral and physiological rhythms to the daily cycle of light and darkness. We have been probing the biochemical substrates of this endogenous pacemaker by examining the ability of treatments affecting cyclic nucleotide-dependent pathways to induce changes in the phase of oscillation in electrical activity of rat SCN isolated in brain slices. Our previous work has shown that daytime treatments that stimulate cAMP-dependent pathways induce phase shifts of the SCN pacemaker in vitro but treatments during the subjective night are without effect. In this study we report that the phase of SCN oscillation is reset by treatments that stimulate cGMP-dependent pathways, but only during the subjective night. Thus, the nocturnal period of SCN sensitivity to cGMP is in antiphase to the diurnal period of sensitivity to cAMP. These results suggest that cAMP and cGMP affect the SCN pacemaker through separate biochemical pathways intrinsic to the SCN. These studies provide evidence that changing biochemical substrates within the SCN circadian clock may underlie some aspects of differential temporal sensitivity of mammals to resetting stimuli.